Banjarese Women’s Language Features: A Gender Study - Jumainah, Jumainah; Krismanti, Ninuk; Lestary, Agustina (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
This research is an attempt to describe the language features of Banjarese women that distinguish them from the ones of men. In this study, the researchers aim to explain the features in a broader setting that is not limited to one specific interaction space. This research is qualitative research. The main instrument of this research is the researchers themselves. Data is collected through transcripts of recorded conversations taking places in three different settings. This research is carried out in South Kalimantan context where the Banjarese language is used in the daily interactions of the people. The data is analyzed using the theory of Female Language Features from Lakoff & Bucholtz (2004) as the research protocol. Some findings of this study contradict the general concepts of language and gender which differentiate the language features of women and men. In daily interactions, Banjarese women and men show supportive or competitive interactions in their conversations. Banjar women can also use harsh words in their interactions with other women or with the opposite sex. However, research with a wider context is needed in the future before concluding that Banjar women and men are equivalent in linguistic behavior.